Non-Oil Trade Openness and Financial Development Impacts on Economic Growth in Saudi Arabia - Aljebrin, Mohammed (International Journal of Economics and Financial Issues, 2018)
This study investigates the relationship between non-oil trade openness and the financial development effect on economic expansion in Saudi Arabia, focusing on the 1990-2016 time period and applying the fully modified ordinary least squares (FMOLS) approach. Non-oil trade openness is represented by the sum of the non-oil exports and imports as a percentage of GDP. Financial market growth is demonstrated by the private sector’s bank credits (the credit market development effect) and the general stock market index (stock market development). In the long run, the findings suggest that the non-oil trade openness, the private sector’s domestic bank credit and the stock market are significant in their expected positive signs. In the short run, the results indicate that Non-oil trade openness and the stock market have an expected positive and significant coefficient but the domestic bank credit offered to the private industry has a noteworthy but negative unexpected sign. The error correction is correctly negatively signed and very significant with a considerable magnitude (-0.268) indicating a speed adjustment process. Consequentially, if the real GDP is out of equilibrium by 1 percent, a 26.8 percent adjustment will occur towards equilibrium by the end of the first year. Keywords: Financial Development, Trade Openness, Economic Growth, FMOLS, Saudi Arabia. JEL Classifications: O11, C22, F11, F14, F41, F43